Natural Care in pregnancy, childbirth and child care: old and new practices, motivations and actors in Portugal and Spain - Neves, D. M. (Mid-term conference da ESA Research Network on the Sociology of Health and Illness, 2016)
This paper results from a research which main goal is to study the increasing adherence to naturalistic and neotraditional values concerning motherhood in Portugal and Spain. This presentation, in particularly, intends to address the importance that mothers and families assign to natural care in pregnancy, delivery and baby care. To do that, we will analyze some exploratory interviews applied to mothers, fathers and professionals who provide a more natural care instead of the conventional medical and care services in the two contexts, so we can identify the main practices and motivations surrounding this naturalistic model of maternity care. Moreover, bringing the comparison between Portuguese and Spanish speeches, this paper also wants to address some social trends and institutional initiatives that concur to distinguish the two countries when it comes to contribute (or not) to the dissemination of a more naturalistic model associated to maternity care.